Pediatric peri-operative fractionated high-dose-rate brachytherapy for recurrent Wilms’ tumor using a reconstructed Freiburg flap - Flower, Emily; Tran, Kathy Ngoc; Zanjani, Salman; Smith, Wayne; Karpelowsky, Jonathan; Summerhayes, Katie; Estoesta, Edgar; Chard, Jennifer (Journal of Contemporary Brachytherapy, 2016)
Purpose : To report peri-operative fractionated high-dose-rate (HDR) brachytherapy with a 3D customized Freiburg flap applicator to treat locally recurrent Wilms’ tumor, followed by immediate hyperthermic intraperitoneal chemotherapy for a 16-year-old with a second recurrence of nephroblastoma (Wilms’ tumor). Material and methods: The tumor was excised and surgical bed was treated with fractionated HDR brachytherapy using a Freiburg flap applicator. Hyperthermic intraperitoneal chemotherapy was performed immediately after the removal of brachytherapy applicator. Results: The Freiburg flap was successfully reconstructed to enable delivery of conformable peri-operative HDR brachytherapy. The clinical target volume (CTV) D90 was 26 Gy in 5 fractions. Conclusions : Peri-operative fractionated HDR brachytherapy with a customized Freiburg flap applicator was delivered successfully across a large multi-disciplinary team.